2014
DOI: 10.1016/j.cortex.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of passive constructions in a patient with primary progressive aphasia

Abstract: Research into agrammatic comprehension in English has described a pattern of impaired understanding of passives and retained ability on active constructions. Some accounts of this dissociation predict that patients who are unable to comprehend actives will also be impaired in the comprehension of passives. We report the case of a man with primary progressive aphasia (WR), whose comprehension was at chance on active sentences, but at ceiling on passives. In a series of reversible sentence comprehension tests WR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…With regard to standard clinical classifications of aphasia syndromes, all participants would be classified as globally aphasic due to the severity of sentence comprehension problems. Standard agrammatic/Broca's aphasia profiles include sensitivity to word order information and, therefore, correct performance on active sentences (Zimmerer, Dąbrowska, Romanowski, Blank, Varley, 2014). The patients we describe as agrammatic differ in that they perform at chance on the comprehension of canonical active sentences of the type 'The boy kissed the girl/The girl kissed the boy'.…”
Section: Language Pathologymentioning
confidence: 89%
“…With regard to standard clinical classifications of aphasia syndromes, all participants would be classified as globally aphasic due to the severity of sentence comprehension problems. Standard agrammatic/Broca's aphasia profiles include sensitivity to word order information and, therefore, correct performance on active sentences (Zimmerer, Dąbrowska, Romanowski, Blank, Varley, 2014). The patients we describe as agrammatic differ in that they perform at chance on the comprehension of canonical active sentences of the type 'The boy kissed the girl/The girl kissed the boy'.…”
Section: Language Pathologymentioning
confidence: 89%
“…Increasing auditory attention deficits seem to have an additional influence on sentence-comprehension abilities in lvPPA (Etcheverry et al 2012). In opposition to the assumptions from Gorno-Tempini et al (2004), Zimmerer et al (2014) reported the case of a man with lvPPA who had more problems understanding active sentence constructions than passive constructions, and could not rule out the possibility that there are grammatical explanations for this phenomenon.…”
Section: Sentence Comprehensionmentioning
confidence: 78%
“…However, we advise caution since many SPM designs, including the design in this study, do not have enough trials for observations at case level to be reliable, especially if differences between performance across trial types are small. Longer SPM designs can start to explore the capacity to reach factive and counterfactive interpretations at an individual level, and may identify individuals with preserved counterfactive interpretation, but impaired factive interpretation capacities, similar to how SPM case studies identified individuals with impaired active, but intact passive voice comprehension (Druks & Marshall, 1995;Zimmerer, Dąbrowska, Romanowski, Blank, & Varley, 2014). Duman et al (2015), who tested aphasic comprehension of factuals and counterfactuals using SPM, suggest that impairment can come both from a disruption of networks for processing morphosyntactic information and networks responsible for "cognitive complexity".…”
Section: Discussionmentioning
confidence: 97%